Application of Augmented Reality Based Freestyle Swimming Material Learning Media for Junior High School Students - Feri Apriani; Rahma Devi; Nurkadri (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This study aims to develop and apply learning media for freestyle swimming material based on augmented reality to junior high school students in the city of Padang Sidempuan. The type of research in this study is qualitative research with development studies used in a research must be based on the issues raised. The research procedure used in this study is in accordance with the steps for using the method Research and Development. The sample used in this study was PJOK teachers in Padang Sidempuan District. The results of this study indicate that out of 10 small group trial samples with a total score of 650 divided by a maximum score of 700 x 100%, it produces a presentation of 92.8% with the following criteria:Very Worth it.The results of the stage 2 trial on teachers are outlined through the formula for the percentage of the number of answers/maximum score x 100% with the following results. Of the 20 samples of the Phase II trial with a total score of 1.505 divided by a maximum score of 1.600 x 100% yield presentation of 94.0% with criteriaVery Worth it.The conclusion in this study is eligibility based learning media augmented reality Freestyle swimming material for PJOK teachers declared appropriate and can be used for PJOK teachers in using media-based learning augmented reality freestyle swimming material.